2023
DOI: 10.3390/pr11020635
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Capital Structure on the Profitability Performance of ICT Firms

Abstract: Information and communication technology (ICT) companies strive for ceaseless innovation to remain competitive while facing the challenge of maximizing firm value (FV) with limited resources, and increasing the interests of shareholders. However, capital structures have a considerable effect on FV, and the literature still disagrees with the optimum structure in specific industries and countries. Therefore, this study evaluates the FV of ICT companies in terms of profitability efficiency using data envelopment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…The regression results showed that capital structure had a positive and significant effect on financial performance of microfinance institutions in Mombasa County, Kenya. The results are consistent with the results of Kim et al (2023) which indicated that capital structure has a positive and significant effect on the profitability performance of firms.…”
Section: Discussion Of Key Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…The regression results showed that capital structure had a positive and significant effect on financial performance of microfinance institutions in Mombasa County, Kenya. The results are consistent with the results of Kim et al (2023) which indicated that capital structure has a positive and significant effect on the profitability performance of firms.…”
Section: Discussion Of Key Findingssupporting
confidence: 91%
“…In the South Korean context, Kim, Jung, and Kim (2023) examined the influence of capital structure on the profitability performance of information and communication technology (ICT) firms. The results indicated that capital structure had a positive and significant effect on the profitability performance of ICT firms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the prior investigations indicate that the Malaysian firms' capital structure holds dynamic properties (Halim et al, 2019). However, few studies investigate dynamic capital structure determinants for Malaysian Shariah-tagged firms and focus more on executing traditional methodology (Abdul Hadi et al, 2015;Kim, Jung, & Kim, 2023;Nejad & Wasiuzzaman, 2013). Therefore, this inquiry selected an efficient econometric estimator, i.e., Generalized Method of Moments(GMM).…”
Section: Methodsmentioning
confidence: 99%
“…As long as the advantages of the tax shelter outweigh the disadvantages of financial difficulty, the trade-off theory predicts that enterprises can raise their value by employing debt financing. (Ahmed et al, 2023;Akinrinola et al, 2023;Akmalia, 2023;Ali et al, 2022;Almomani et al, 2022;Hussein, 2020;Irawan et al,2022;Kim et al, 2023;Maina & Jagongo, 2022;Maneerattanarungrot & Donkwa, 2018;Mills & Mwasambili, 2022;Ngoc et al, 2021;Oktrima & Sutrisno,2023;Olusola et al, 2022). However, a few studies found insignificant or adverse effects of capital structure on firm performance (Pandey & Sahu, 2023;Sakr & Bedeir, 2020).…”
Section: The Relation Between Capital Structure and Firm Performancementioning
confidence: 99%
“…Managers, stockholders, and creditors all having competing interests can lead to agency costs that reduce firm performance and increase the cost of debt. When certain parties have access to more or better knowledge than others, it can lead to issues with adverse selection and moral hazard when attracting outside funding (Hussein, 2020;Irawan et al,2022;Kim et al,2023).…”
Section: The Relation Between Capital Structure and Firm Performancementioning
confidence: 99%